Attachment systems for mandibular implant-supported overdentures: A systematic review and meta-analysis of randomized controlled trials - Prasad, Soni; Faverani, Leonardo P. [UNESP]; Santiago Junior, Joel Ferreira; Sukotjo, Cortino; Yuan, Judy Chia-Chun (Elsevier, 2022)
Statement of problem: Although mandibular implant-supported overdentures have been highly recommended as a treatment option, a consensus on the type of attachment systems that can be used to increase implant and prostheses survivability is lacking. Purpose: The purpose of this systematic review and meta-analysis was to compare different types of attachments for retention by investigating outcome measures such as implant and prosthesis survival rates and biological and prosthesis complications in participants with a mandibular implant-supported overdenture. Material and methods: The search was performed in the PubMed, Cochrane, Embase, and Scopus databases by following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses criteria and registered with the International Prospective Register of Systematic Reviews (CRD42021253566). An analysis of association was conducted between different attachment systems and implant and overdenture survival rates in randomized controlled clinical trials. Results: The initial search indicated 477 studies, of which 25 randomized controlled trials (RCTs) were included for analysis. A total of 2154 implants and 737 overdentures were analyzed in the meta-analysis. The main results indicated the failure rate for dental implants to be 2.0% (95% confidence interval [CI], 1.3 to 3.2) and overdentures 4.2% (95% CI, 1.6 to 10.5), respectively. With regard to different attachment systems, a similar failure rate was identified with bar-type retention (7.7% to 95% CI, 3.0 to 18.1), magnetic retention systems (7.6% to 95% CI, 2.2 to 22.7), and ball-type retention (6.8% to 95% CI, 3.0 to 14.3). No significant difference was found in biological complications for splinted and unsplinted implant overdentures (P=.902). Regarding prosthetic complications, the most favorable groups were LOCATOR attachments followed by telescopic and Conus, bar, and ball attachments. Magnet attachments had higher prosthetic complications (7.4 times) than the other attachments. Conclusions: Implants and implant-supported mandibular overdentures showed a high survival rate irrespective of the attachment system used. Splinting implants did not significantly affect the rate of biological complications. Prosthetic complications were most common for magnet and least common for LOCATOR attachments.